An overview on synthetic strategies for the construction of star-shaped molecules. Issue 29 (30th May 2019) - Diab, Hadeer M.; Abdelmoniem, Amr M.; Shaaban, Mohamed R.; Abdelhamid, Ismail A.; Elwahy, Ahmed H. M.
Abstract : This review summarizes the strategies for the synthesis of star-shaped molecules as well as their specific syntheses. Abstract : Strategies for the synthesis of star-shaped molecules have been in high demand in the last decades due to the importance of those compounds in various fields. The distinctly different properties of these compounds compared to their linear analogues make them versatile building blocks for the formation of mesophases of interesting mesomorphic and photophysical properties. Moreover, the applications of star-shaped molecules as building units for dendrimers as well as in supramolecular host–guest chemistry have also been recently studied. The star-shaped molecules mentioned in this review are classified according to the central core as well as the type of side arms. The properties and applications of these compounds are described in the appropriate contexts. This report summarizes the recent advances in this area.